The role of the school council in Municipal Elementary Schools (EMEF) in Vitória, in State of Espírito Santo, Brazil (Research, Society and Development, 2021)
The article aims to analyze one of the mechanisms of Democratic Management – the School Council, under the perception of this collegiate body. Applies a qualitative methodology with semi-structured interviews to the holders of the School Councils in four Municipal Schools of Elementary Education, using the content analysis of Bardin. Noteworthy are the registration units: participation, strengthening, sharing, conversation, criticism, among others. The simple statistic showed the direct relationship of 1-Council, 2-Participate and 3-Democratic Management, totaling the percentage of 40.41% of frequencies, and the School Board is the collegiate body that must manage the school.